2012
DOI: 10.1007/978-3-642-25926-5_8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Detection of Building Patterns in Cartographic Data: Two Algorithms

Abstract: ABSTRACT:Building patterns are important features in applications like automated generalization and spatial data mining. Many previous work has however focused on a few specific patterns (i.e. collinear pattern), while many others are less discussed. This paper proposes a comprehensive typology of available building patterns through the study of existing maps, and discusses their characteristics. This typology includes collinear, curvilinear, align-along-road, grid-like and unstructured patterns. Two algorithm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 9 publications
(18 reference statements)
3
27
0
Order By: Relevance
“…1), buildings are regarded as vertices and any two buildings that share at least one triangle are regarded as proximal, and an edge forms between the centroids of these two buildings. The detailed instruction and discussion of proximity graph can be referred in references (Zhang et al 2010(Zhang et al , 2013. 2 Proximity graph refinement Proximity graph only reflects the topological proximity of buildings, even two distant buildings may have the proximity relationship, which has less benefits to the further analyzing.…”
Section: Proximity Graph Of Area Featurementioning
confidence: 99%
“…1), buildings are regarded as vertices and any two buildings that share at least one triangle are regarded as proximal, and an edge forms between the centroids of these two buildings. The detailed instruction and discussion of proximity graph can be referred in references (Zhang et al 2010(Zhang et al , 2013. 2 Proximity graph refinement Proximity graph only reflects the topological proximity of buildings, even two distant buildings may have the proximity relationship, which has less benefits to the further analyzing.…”
Section: Proximity Graph Of Area Featurementioning
confidence: 99%
“…Regnault [12], Yan et al [13], Steinhauer et al [14] and Qi and Li [15] all proposed methods for the grouping of buildings. Zhang et al [16] proposed a categorization of building patterns which includes collinear, curvilinear, align-along-road, grid-like and unstructured. The detection of collinear building patterns has been extensively studied [17,18].…”
Section: Implicit Spatial Informationmentioning
confidence: 99%
“…The detection of collinear building patterns has been extensively studied [17,18]. Zhang et al [16] proposed algorithms for detecting align-along-road and unstructured building patterns. Luscher et al [19] demonstrated that higher level semantics, such as terraced house, can be derived from building alignments and other criteria.…”
Section: Implicit Spatial Informationmentioning
confidence: 99%
“…In addition, the computation of nearest distance between buildings and between buildings and roads on this structure becomes more efficient [33]. This step results in initial proximity graph.…”
Section: 2mentioning
confidence: 99%
“…clusters) [33], distinguishing between linear alignments (collinear, curvilinear and alignalong-road) and nonlinear clusters (grid-like and unstructured), see Fig. 1.…”
Section: Related Workmentioning
confidence: 99%